The putative lithium-mimetic ebselen reduces impulsivity in rodent models. (September 2018) - Barkus, Chris; Ferland, Jacqueline-Marie N; Adams, Wendy K; Churchill, Grant C; Cowen, Philip J; Bannerman, David M; Rogers, Robert D; Winstanley, Catharine A; Sharp, Trevor
Background: Deficits in impulse control feature in many psychiatric conditions including bipolar disorder, suicidality and addictions. Lithium lowers impulsivity in clinical populations and decreases pathological gambling in experimental medicine studies, but suffers from adverse effects, poor compliance and a low therapeutic index. Aims: Recently we identified that the neuroprotective agent ebselen, which is reportedly safe in humans, inhibited inositol monophosphatase (IMPase), a candidate lithium mechanism. Ebselen also reduced 5-HT receptor (5-HT2A ) function which predicts impulsivity lowering properties. Here we investigated the effect of ebselen in rat models of impulsive behaviour. Methods: Ebselen was tested in two models of impulsivity with human analogues: the five-choice serial reaction time task (5-CSRTT) and rodent gambling task (rGT). The main outcome measures were premature responses (5-CSRTT and rGT) and choice behaviour (rGT), which model motor impulsivity and choice impulsivity, respectively. Results: At doses that decreased 5-HT2A receptor function (DOI-induced wet dog shakes), ebselen decreased premature responding in the 5-CSRTT both in the absence and presence of cocaine. The 5-HT2A receptor antagonist MDL 100, 907 also reduced premature responding in the 5-CSRTT although not in the presence of cocaine. In the rGT ebselen showed a tendency to reduce premature responding but had no effect on choice behaviour. Conclusions: These findings suggest that ebselen preferentially reduces motor impulsivity over choice impulsivity, and that inhibition of 5-HT2A receptor function is a contributing mechanism. Collectively, these data support the repurposing of ebselen as an anti-impulsive treatment and fast-tracking to clinical trials in patient groups characterised by poor impulse control.